Disturbance ecology and size class structure of the Mulanje cedar of Malawi, Widdringtonia whytei and associated broadleaved forest - Burger, Niel (Department of Biological Sciences, 2017)
The disturbance ecology and regeneration patterns of the emergent conifer, Widdringtonia whytei, and five broadleaved species, Aphloia theiformis, Rapanea melanophloeos, Maesa lanceolata, Maytenus accuminata and Psychotria mahonii, were inferred from population size structures in the mixed conifer-broadleaved forests of Mt. Mulanje, Malawi. The size-class structures of the emergent cedar populations were characterised by even-sized, disjunct frequency distributions. Seedling recruitment was found in recently burnt sites and not in middle-aged or oldgrowth forest. This indicates reliance on the catastrophic mode of regeneration for W. whytei, which takes advantage of the well-lit, competition free environment after large-scale disturbances provided by fire. The sub-canopy angiosperms primarily had all-sized frequency distributions, with at least some individuals found in each class within their size range, indicating continuous regeneration under a closed forest canopy. These results emphasize the dependence of long-lived conifers such as the Mulanje cedar on large-scale disturbance for regeneration and long-term persistence of the species.